Association of age with clinical features and ablation outcomes of paroxysmal supraventricular tachycardias. Issue 14 (11th October 2021) - Ávila, Pablo; Calvo, David; Tamargo, María; Uribarri, Aitor; Datino, Tomas; Arenal, Angel; Atienza, Felipe; Soto, Nina; Fernández-Avilés, Francisco; González-Torrecilla, Esteban
Abstract : Objective: The role of age in clinical characteristics and catheter ablation outcomes of atrioventricular nodal re-entrant tachycardia (AVNRT) or orthodromic atrioventricular re-entrant tachycardia (AVRT) has been assessed in retrospective studies categorising age by arbitrary cut-offs, but contemporary analyses of age-related trends are lacking. We aimed to study the relationship of age with epidemiological, clinical features and catheter ablation outcomes of AVNRT and AVRT. Methods: We recruited 600 patients (median age 56 years, 60% female) with a confirmed diagnosis of AVNRT (n=455) or AVRT (n=145) by means of an electrophysiological study. They were interrogated for arrhythmia-related symptoms with a structured questionnaire and followed up to 1 year. We analysed age as a continuous variable using regression models and adjusting for relevant covariables. Results: Both typical and atypical forms of AVNRT upraised with age while AVRT decreased (p<0.001 by regression). Female sex predominance in AVNRT was not observed in older patients. Overall, these tachycardias became more symptomatic with ageing despite a longer tachycardia cycle length (p<0.001) and regardless of the presence of structural heart disease, with a higher proportion of dizziness, syncope, chest pain or dyspnoea (p<0.005 for all) and a lower presence of palpitations or neck pounding (p<0.001 for both). Age was not associated with catheter ablation acute success, periprocedural complications or 1-year recurrence rates (p>0.05 for all). Conclusions: Age, evaluated as a continuous variable, had a significant association with the clinical profile of patients with AVNRT and AVRT. Nevertheless, catheter ablation outcomes and complications were not significantly related to patients' age.